EVALUATION OF DRINKING WATER QUALITY AT VARIOUS PUBLIC PLACES IN LAHORE CITY PAKISTAN - M. Jibreel; A. Ahmad; M. Rabbani; H. Mushtaq; A. Ghafoor; M. Z. Shabbir; M. H. Saleem; M. K. Saleemi; M. Avais; J. Muhammad; H. Rehman (Journal of Animal and Plant Sciences, 2018)
Fifty eight water samples in triplicate were collected from tap and filtration units from selected sites of various public places including universities and colleges in Lahore city. All collected samples were tested for status of physicochemical parameters ( pH, turbidity, hardness and total dissolved solids, arsenic, nitrite and fluoride) and presence of indicator bacteria (total coliform and fecal coliform) and compared with World Health Organization (WHO) standards for drinking water. The results demonstrated that physicochemical quality of drinking water was satisfactory except arsenic and fluoride in few water samples. The microbial quality of water has breached the WHO standard limits. The statistical analysis using one way ANOVA, a significant difference in microbial quality, nitrite and total hardness was observed among various public places ( p<0.05) irrespective of animal parks, recreational parks, historical places, public transport stations and Universities. However, a non-significant difference ( p>0.05) was found when data of physiochemical analysis ( turbidity, pH, TDS, arsenic, fluoride) was compared. Water related health problems are more common
Keywords: Microbial; physiochemical analysis; Public places; Water quality; ZOO